Implant-retained thumb prosthesis with anti-rotational attachment for a geriatric patient - Goiato, Marcelo Coelho [UNESP]; Garcia-Junior, Idelmo Rangel [UNESP]; Magro Filho, Osvaldo [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Wiley-Blackwell, 2010)
This report presents the use of a dental implant with an anti-rotational attachment for the retention of a thumb prosthesis. A retention system was manufactured with an attachment (UCLA) screwed into the implant with a two-bar system that was cast in metallic silver palladium. A substructure made from heat-cured acrylic resin was joined to the retention system by clips to join the thumb to the finger (bar clip) in the cast with implant rejoinder. The silicone material, Silastic-MDX 44210, was used to achieve function and aesthetics. Following osseointegration, no skin problems were observed. Whilst the implant-retained digital prosthesis presented some motor limitations, it allowed the patient to return to entertainment and achieve social conviviality.
Keywords: thumb prosthesis; implant; retention system